OASIS evaluation of the French surveillance network for antimicrobial resistance in diseased animals (RESAPATH): success factors underpinning a well-performing voluntary system. (20th April 2021) - Mader, R.; Jarrige, N.; Haenni, M.; Bourély, C.; Madec, J.-Y.; Amat, J.-P.
Abstract: Antimicrobial resistance is a One Health issue requiring the development of surveillance systems in the human, environmental and animal sectors. In the European Economic Area, the surveillance of antimicrobial resistance in zoonotic pathogens and indicator bacteria in healthy food-producing animals is required legally, while countries are also expected to extend their surveillance to diseased animals in the frame of national action plans. In this context, evaluating existing antimicrobial resistance surveillance systems in animal health is important to improve systems in place, but also to help other countries learn from these experiences, understand success factors and anticipate challenges. With this aim, the French surveillance network for antimicrobial resistance in bacteria from diseased animals (RESAPATH) was evaluated using the Outil d'Analyse des Systèmes d'Information en Santé (OASIS) assessment tool. Key performance factors included (i) a strong and inclusive central institutional organisation defining clear and well-accepted surveillance objectives, scope and procedures, (ii) strong skills in epidemiology and microbiology and (iii) a win–win approach enabling the voluntary participation of 71 field laboratories and where free annual proficiency testing plays a pivotal role. The main area for improvement of RESAPATH was its time-consuming data management system.